Development of Culturally-Based Listening Skill Teaching Materials in Arabic Language Instruction at MTs Nurul Falah Pamekasan - Yuswandi, Yuswandi; Wargadinata, Wildana; Fikri, Shofil (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2025)
In the context of the massive wave of globalization that has the potential to erode cultural identity, the field of education is required not only to serve as a medium for the transfer of knowledge, but also as a strategic instrument in preserving local cultural values. This research aims to describe: (1) the development process of locally-based listening materials for Arabic language instruction at Madrasah Tsanawiyah in Pamekasan, (2) to determine the validity of the developed materials, and (3) to assess their effectiveness in improving students’ listening skills. The research method employed in this study is Research and Development (R&D) using the ADDIE model, which consists of five stages: needs analysis, product design, product development, product implementation, and product evaluation. The data collection techniques used by the researcher include observation and interviews with qualitative data analysis, while questionnaires and tests are analyzed using quantitative methods through the Likert scale and the Paired Sample t-test. The results of the study indicate that: The process of preparing the teaching materials begins with the stage of analyzing students' needs using questionnaires and teacher interviews. The teaching materials are then designed in the form of a book. The development of listening skill teaching materials based on local wisdom received a score of 94% from the material validation, 92% from the language validation, and 91% from the design validation. Regarding the effectiveness of the product, using pre-tests and post-tests, the researcher obtained a result of 53.789, which is greater than the t-value at 0.05, thus the null hypothesis Ho is rejected. This indicates a significant change after the product trial, and the teaching material is effective in improving students' Arabic listening skills.